Kepemimpinan Kepala Sekolah dan Kompensasi: Analisa Regresi pada Kinerja Guru - Eko Sunanto; Wresni Pujiyati; Ahmad Dasuki Aly (Journal of Education and Teaching (JET), 2022)
This study aims to describe the effect of principal's leadership and compensation on teacher performance. The research method used was descriptive and verification methods. The data collection technique was done by asking 45 teachers from 6 schools to fill out a questionnaire with a Likert scale. Processing of research results using regression analysis techniques. Significance test using f-test. The results showed that: the leadership of the principal has a positive and significant effect on teacher performance. Compensation has a positive and significant effect on teacher performance. Meanwhile, the principal's leadership and compensation simultaneously (simultaneously) have a positive and significant effect on teacher performance. The results of data analysis showed that the principal's leadership on teacher performance an average of 51.7% had a positive and significant influence. Compensation for teacher performance an average of 20.1% has a positive and significant effect. Principal leadership and compensation (simultaneously) on teacher performance an average of 62.1% have a positive and significant effect. Thus, the researcher concludes that principal's leadership and compensation have a positive effect on teacher performance.